Peran Budaya dalam Pembentukan Identitas Regional di Asia Tenggara - Oot Hotimah; Amelia Veviani; Sri Rahmawati; Ziyanah Walidah (Universitas Syiah Kuala, Banda Aceh, 2025)
Southeast Asia is a region rich in cultural diversity, shaped by the interaction of various ethnic groups, races, and external civilizations. This article examines the role of culture in shaping regional identity in Southeast Asia, highlighting aspects such as language, beliefs, cuisine, arts, architecture, and social values that characterize the region. Based on literature studies, it was found that Malay culture serves as the primary foundation of Southeast Asian culture, strongly influenced by Chinese, Indian, and Islamic traditions. This shared cultural identity plays a crucial role in strengthening unity and cohesion among ASEAN nations. A deeper understanding of the region's culture is expected to enhance social integration and preserve diversity as a valuable asset in the global dynamic. Abstrak Asia Tenggara merupakan kawasan yang kaya akan keberagaman budaya yang terbentuk dari interaksi berbagai suku, ras, dan pengaruh peradaban luar. Artikel ini membahas peran budaya dalam pembentukan identitas regional di Asia Tenggara, dengan menyoroti aspek bahasa, kepercayaan, kuliner, seni, arsitektur, serta nilai sosial yang menjadi ciri khas kawasan ini. Berdasarkan studi literatur, ditemukan bahwa budaya Melayu menjadi akar utama budaya di Asia Tenggara, dengan pengaruh kuat dari Tiongkok, India, dan Islam. Identitas regional yang terbentuk dari kesamaan budaya ini berperan dalam memperkuat rasa persatuan dan kebersamaan di antara negara-negara ASEAN. Pemahaman mendalam mengenai budaya di kawasan ini diharapkan dapat memperkuat integrasi sosial dan menjaga keberagaman sebagai aset penting dalam dinamika global.